Urease Inhibitors of Agricultural Interest Inspired by Structures of Plant Phenolic Aldehydes - Horta, Lívia; Mota, Yane; Barbosa, Gisele; Braga, Taniri; Marriel, Ivanildo; de Fátima, Ângelo; Modolo, Luzia (Journal of the Brazilian Chemical Society, 2016)
The plant phenolic natural products (PNPs) protocatechuic aldehyde, syringaldehyde and vanillin were used as platforms for obtaining four urease inhibitors. Urea (urease substrate) or thiourea (urease inhibitor) core was added to the structure of newly synthesized compounds to provide inhibitors up to 230-fold more active than the PNPs they originated from. The PNP derivatives are mixed inhibitors with higher affinity to urease active site. Two compounds were as efficient as N-(butyl)thiophosphoric triamide (NBPT) toward soil. Overall, PNPs derivatives are promising urease inhibitors for use as additive in urea-based fertilizers formulations.